2019
DOI: 10.3390/nu11030622
|View full text |Cite
|
Sign up to set email alerts
|

Red and Processed Meat and Mortality in a Low Meat Intake Population

Abstract: Associations of low-to-moderate consumption of red and processed meat with mortality would add to the evidence of possible adverse effects of these common foods. This study aims to investigate the association of red and processed meat intake with mortality. The Adventist Health Study-2 (AHS-2) is a prospective cohort study of ~96,000 Seventh-day Adventist men and women recruited in the US and Canada between 2002 and 2007. The final analytic sample after exclusions was 72,149. Cox proportional hazards regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 52 publications
0
27
1
1
Order By: Relevance
“…Interestingly, our study found that the increased risks of death from CVD and heart disease were more pronounced in women. Similarly, previous studies also observed that consumption of soft drinks and processed meat was positively associated with higher CVD incidence and mortality in women than in men [47][48][49]. In fact, sex difference in cardiovascular outcomes has long been recognized [50].…”
Section: Explanations For Sex Difference In Cardiovascular Mortalitymentioning
confidence: 69%
“…Interestingly, our study found that the increased risks of death from CVD and heart disease were more pronounced in women. Similarly, previous studies also observed that consumption of soft drinks and processed meat was positively associated with higher CVD incidence and mortality in women than in men [47][48][49]. In fact, sex difference in cardiovascular outcomes has long been recognized [50].…”
Section: Explanations For Sex Difference In Cardiovascular Mortalitymentioning
confidence: 69%
“…Since phosphatidylcholine/choline and/or l-carnitine are important sources of TMA via the gut microbiota [5][6][7], it has been postulated that the consumption of these TMA precursors (i.e., red meat) might be a critical factor promoting the risk of CVD development [49]. In contrast with this hypothesis, numerous studies investigating the biological effects of these nutrient supplementations did not support their positive association with CVD [50], suggesting that the relationship between nutritional intake of choline and l-carnitine and CVD could be more complex than as initially hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Those conditions increase premature death and disability. There is a conceptual model about how red meat and alcohol consumption increase premature mortality based on American addiction center resource 2018 [41] and the study of Saeed Mastour Alshahrani et al in 2019 [42] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%